EFEKTIFITAS PENGGUNAAN MEDIA PEMBELAJARAN DARING DALAM PEMBELAJARAN KIMIA PADA MASA PANDEMI - Nurmalahayati Nurdin; Haris Munandar; Hanifatussyifa Hanifatussyifa; Ulfa Yusriani (UIN AR-RANIRY, 2022)
This study aims to describe the effectiveness of the chemistry learning process by using online methods, the challenges and the advantages of using media in learning chemistry. This research was conducted at several high schools in Aceh with a sample of 70 people, of which consist 60 students and 10 teachers. Based on the results of the data analysis, it can be concluded that in the time of the pandemic, the use of media online has signigficanntly increased, but about 35.3% of the respondents mentioned that the use of media online for teaching chemistry is not very effective. However, the advantages of using media online in teaching chemistry during the pandemic Covid-19 are to help avoid the spreading of the virus Covid-19.